1999
DOI: 10.1038/5583
|View full text |Cite
|
Sign up to set email alerts
|

Salt–sensitive hypertension and reduced fertility in mice lacking the prostaglandin EP2 receptor

Abstract: Prostaglandins (PGs) are ubiquitous lipid mediators derived from cyclooxygenase metabolism of arachidonic acid that exert a broad range of physiologic activities, including modulation of inflammation, ovulation and arterial blood pressure. PGE2, a chief cyclooxygenase product, modulates blood pressure and fertility, although the specific G protein-coupled receptors mediating these effects remain poorly defined. To evaluate the physiologic role of the PGE2 EP2 receptor subtype, we created mice with targeted dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
251
3
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(271 citation statements)
references
References 15 publications
13
251
3
2
Order By: Relevance
“…While EP 1 , FP and TP receptors are each broadly classified as members of the contractile subgroup of prostanoid receptors , functionally they are primarily associated with distinct physiologic processes and each exhibit distinct patterns of expression Sugimoto et al, 2000). Consistent with the latter, mice deficient in each of these receptors display unique characteristic phenotypes including a reduction in carcinogen-induced colorectal cancer in EP 1 -deficient mice (Ushikubi et al, 1998;Watanabe et al, 1999;Sugimoto et al, 2000), loss of parturition affecting both ovulation and fertilization in FPdeficient mice Hizaki et al, 1999;Kennedy et al, 1999) and increased bleeding tendency associated with TP-deficient mice (Thomas et al, 1998). While EP 1 , FP and TP receptors are also abundantly expressed in the kidney (Sugimoto et al, 2000) and they are each reported to mediate efficient contraction of renal vascular SM and mesangial cells through Ca 2 þ -dependent mechanisms (Mene et al, 1989), their role in renal function as garnered from mouse knockout studies remains to be clearly established.…”
Section: Discussionmentioning
confidence: 97%
“…While EP 1 , FP and TP receptors are each broadly classified as members of the contractile subgroup of prostanoid receptors , functionally they are primarily associated with distinct physiologic processes and each exhibit distinct patterns of expression Sugimoto et al, 2000). Consistent with the latter, mice deficient in each of these receptors display unique characteristic phenotypes including a reduction in carcinogen-induced colorectal cancer in EP 1 -deficient mice (Ushikubi et al, 1998;Watanabe et al, 1999;Sugimoto et al, 2000), loss of parturition affecting both ovulation and fertilization in FPdeficient mice Hizaki et al, 1999;Kennedy et al, 1999) and increased bleeding tendency associated with TP-deficient mice (Thomas et al, 1998). While EP 1 , FP and TP receptors are also abundantly expressed in the kidney (Sugimoto et al, 2000) and they are each reported to mediate efficient contraction of renal vascular SM and mesangial cells through Ca 2 þ -dependent mechanisms (Mene et al, 1989), their role in renal function as garnered from mouse knockout studies remains to be clearly established.…”
Section: Discussionmentioning
confidence: 97%
“…COX-2-knockout mice on CD1d background [38] and EP2 receptor-knockout mice on C57BL/6 background [39] were used for the experiments. Control mice on CD1d and C57BL/6 background were purchased from Charles River Laboratory.…”
Section: Animal Modelmentioning
confidence: 99%
“…For experiments, males and females with deletion of one EP2 receptor allele (Het) were crossed to obtain KO, Het and WT littermates. EP2 receptor KO mice were initially in C57BL/6 X 129 background {the kind gift of Richard M. Breyer, Vanderbilt University Medical Center, Nashville, 1999, [10]} and were backcrossed more than 9 generations into the C57BL/6 background. Genotyping protocols were followed as described previously [11].…”
Section: Animalsmentioning
confidence: 99%